Corynebacterium pseudotuberculosis Pneumonia in a Veterinary Student Infected During Laboratory Work. (15th April 2015) - Heggelund, Lars; Gaustad, Peter; Håvelsrud, Othilde Elise; Blom, Jochen; Borgen, Lars; Sundset, Arve; Sørum, Henning; Frøland, Stig Sophus
Abstract: We present a case of Corynebacterium pseudotuberculosis pneumonia in a veterinary student, with molecular genetic evidence of acquisition during laboratory work, an observation relevant for laboratory personnel working with C pseudotuberculosis isolates. The patient was clinically cured with 14 months trimethoprim/sulfamethoxazole and rifampicin combination treatment.